Essential Mineral Intake During Pregnancy and Its Association With Maternal Health and Birth Outcomes in South East Queensland, Australia. (September 2019) - McAlpine, Janelle M; McKeating, Daniel R; Vincze, Lisa; Vanderlelie, Jessica J; Perkins, Anthony V
Micronutrient supplements are often recommended during pregnancy, yet their role and necessity remain poorly understood in the Australian population. This study aimed to determine the essential mineral intake of a population of pregnant women in South East Queensland and investigate the effects of supplements on their micronutrient status and birth outcomes. Women completing the Oral Glucose Tolerance Test at two South East Queensland hospitals between 180 and 210 days gestation provided fasting blood samples and dietary data using the Maternal Outcomes and Nutrition Tool (n = 127). Birth outcomes were sourced from medical records. Serum elemental profiles were determined by inductively coupled plasma mass spectrometry (ICP-MS) analysis. Intake of 8 essential minerals was compared with Australian dietary recommendations; matched serum mineral levels were compared with the current Queensland pregnancy reference ranges. Data were examined using cross-sectional cohort design and independent sample t -tests. Supplement use had no significant influence on serum values of trace elements or the incidence of hypertensive disorders, gestational diabetes, preterm birth or infant birthweight. Dietary selenium, zinc and iodine were significantly higher in women birthing beyond 41 completed weeks; selenium ( P = .026) and zinc ( P = .034) both made unique contributions to the regression models when controlling for confounders. Women exhibited adequate to excessive serum micronutrient levels compared with pregnancy reference ranges, a finding consistent with dietary intake calculations. Data suggest that excessive essential mineral intake contributed to prolonged pregnancy in this cohort, supporting previous studies in this population. Further research is required to determine individual needs and eliminate the potential for harm before recommending pregnancy supplements.